Diffusion kurtosis imaging does not improve differentiation performance of breast lesions in a short clinical protocol - Palm, Theresa; Wenkel, Evelyn; Ohlmeyer, Sabine; Janka, Rolf Matthias; Uder, Michael; Weiland, Elisabeth; Bickelhaupt, Sebastian; Ladd, Mark E.; Zaitsev, Maxim; Hensel, Bernhard; Laun, Frederik Bernd (Magnetic Resonance Imaging, 2019)
Background: Diffusion weighted magnetic resonance imaging (DWI) is known to differentiate between malignant and benign lesions via the apparent diffusion coefficient (ADC). Here, the value of diffusion kurtosis imaging (DKI) for differentiation and further characterization of benign and malignant breast lesions and their subtypes in a clinically feasible protocol is investigated. Material and methods: This study included 85 patients (with 68 malignant and 73 benign lesions) who underwent 3 T breast DWI using three b values (50, 750, 1500 s/mm2), with a total measurement time < 5 min. ADC maps were calculated from b values 50, 750 s/mm2. The diffusion kurtosis model was fitted to the diffusion weighted images, yielding in each lesion the average kurtosis-corrected diffusion coefficient DK and mean kurtosis K. Histopathology was obtained of radiologically suspicious lesions; follow-up scans were used as a standard of reference for benign appearing lesions. Receiver operating characteristic curves were used to evaluate the parameters' diagnostic performance for differentiation of lesion types and grades. The difference in diffusion parameters between subgroups was analysed statistically using the Wilcoxon rank sum test and Kruskal-Wallis test, applying a Bonferroni correction for multiple testing where necessary. Results: ADC, DK and K showed significant differences between malignant and benign lesions (p < 10−5). All parameters had similar areas under the curve (AUC) (ADC: 0.92, DK: 0.91, K: 0.89) for differentiation of malignant and benign lesions. Sensitivity was highest for ADC (ADC: 0.96, DK: 0.94, K: 0.93), as well as specificity (ADC: 0.85, DK: 0.82, K: 0.82). ADC and DK showed significant differences between tumor histologic grades (p = 6.8⋅10−4, p = 6.6 · 10−5, respectively), whereas K did not (p = 0.99). All three parameters differed significantly between subtypes of benign lesions (ADC: p < 10−5, DK: p< 10−5, K: p = 4.1·10−4), but not between subtypes of malignant lesions (ADC: p = 0.21, DK: p = 0.25, K: p = 0.08). Conclusion: DKI parameters and conventional ADC can differentiate between malignant and benign lesions. Differentiation performance was best for ADC. Different tumor grades were significantly different in ADC and DK, which may have an impact on therapy planning and monitoring. In our study, K did not add value to the diagnostic performance of DWI in a clinical setting.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Breast neoplasms; Diagnostic imaging; Diffusion kurtosis imaging; Diffusion magnetic resonance imaging; Neoplasms by histologic type

Doping of 4H-SiC with group IV elements - Krieger, Michael; Rühl, Maximilian; Sledziewski, Tomasz; Ellrott, Günter; Palm, Theresa; Weber, Heiko B.; Bockstedte, Michel Georg (Materials Science Forum, 2016)

Simultaneous Multislice Echo Planar Imaging for Accelerated Diffusion-Weighted Imaging of Malignant and Benign Breast Lesions - Ohlmeyer, Sabine; Palm, Theresa; Janka, Rolf Matthias; Weiland, Elisabeth; Uder, Michael; Wenkel, Evelyn; Laun, Frederik Bernd (Investigative Radiology, 2019)
Objectives Comparison of the diagnostic value of simultaneous multislice (SMS) accelerated diffusion-weighted echo planar imaging (EPI) of malignant and benign lesions of the breast compared with a reference EPI sequence. Materials and Methods The study was approved by the institutional ethics committee. Sixty-eight patients were examined with a diffusion-weighted EPI (reference EPI; TE = 54 milliseconds; TR = 9000 milliseconds; TA, 3:27 minutes) and a diffusion-weighted SMS accelerated EPI (SMS EPI; acceleration factor 2; TE = 58 milliseconds; TR = 4300 milliseconds; TA, 1:53 minutes) in addition to the standard magnetic resonance imaging (MRI) protocol. Further acquisition parameters were as follows: 3 T MAGNETOM Skyra (Siemens Healthcare, Erlangen, Germany), 2.5-mm isotropic resolution, field of view = 185 to 190 × 350 mm2, 62 slices, b = 50 and 800 s/mm2 with 1 and 4 averages, respectively. A dedicated 16-channel bilateral breast coil was used for imaging. Image quality was evaluated with respect to the presence of artifacts, signal voids, and quality of fat suppression. These parameters were rated using a 5-point Likert scale (1 = very strong to 5 = negligible). The apparent diffusion coefficient (ADC) was measured in 72 focal lesions (46 breast carcinomas and 26 benign lesions), and the diagnostic value of the 2 datasets was statistically evaluated and compared. The evaluation was performed a second time excluding cysts. Results Artifacts and signal voids were negligible in both sequences (mean on Likert scale for reference EPI 4.68 vs SMS EPI 4.65, P = 0.52, and mean on Likert scale for reference EPI 4.85 vs SMS EPI 4.77, P = 0.14). Fat suppression was significantly better in SMS EPI (mean on Likert scale 3.28 vs 2.97, P < 0.001, Pearson r = 0.49). For benign lesions, the mean ADC in both EPI sequences was 1.86 · 10-3 mm2/s. For malignant lesions, a mean ADC of 0.90 · 10-3 mm2/s for the reference EPI and 0.89 · 10-3 mm2/s for the SMS EPI was found. No significant difference between the EPI sequences was observed for ADC values (P = 0.75) and for the area under the curve (SMS, 0.985; no SMS, 0.975). The cutoff for differentiation of benign and malignant lesions was at ADC = 1.42 · 10-3 mm2/s for SMS EPI (sensitivity, 1; specificity, 0.88) and at 1.23 · 10-3 mm2/s for the reference EPI (sensitivity, 1; specificity, 0.92). Excluding the cysts, the cutoff for differentiation of benign and malignant lesions was at ADC = 1.11 · 10-3 mm2/s for SMS EPI (sensitivity, 0.89; specificity, 0.93) and at 1.23 · 10-3 mm2/s for the reference EPI (sensitivity, 1; specificity, 0.87). Conclusions Our data indicate that SMS acceleration can be used for diffusion imaging in breast MRI in clinical practice. Simultaneous multislice EPI achieved the same diagnostic accuracy in breast MRI, but in a substantially reduced scan time.
CRIS-Team Scopus Importer:2019-07-26
Keywords: breast; diffusion; DW MRI; DWI; EPI; lesions; simultaneous multislice acceleration; SMS

Ultra-High b-Value Diffusion-Weighted Imaging-Based Abbreviated Protocols for Breast Cancer Detection - Ohlmeyer, Sabine; Laun, Frederik Bernd; Bickelhaupt, Sebastian; Palm, Theresa; Janka, Rolf Matthias; Weiland, Elisabeth; Uder, Michael; Wenkel, Evelyn (Investigative Radiology, 2021)
Objectives Contrast-enhanced (CE) magnetic resonance imaging (MRI) is the most effective imaging modality for breast cancer detection. A contrast agent-free examination technique would be desirable for breast MRI screening. The purpose of this study was to evaluate the capability to detect and characterize suspicious breast lesions with an abbreviated, non-contrast-enhanced MRI protocol featuring ultra-high b-value diffusion-weighted imaging (DWI) compared with CE images. Materials and Methods The institutional review board-approved prospective study included 127 female subjects with different clinical indications for breast MRI. Magnetic resonance imaging examinations included DWI sequences with b-values of 1500 s/mm(2) (b1500) and 2500 s/mm(2) (b2500), native T1- and T2-weighted images, and CE sequences at 1.5 T and 3 T scanners. Two reading rounds were performed, including either the b1500 or the b2500 DWI in consecutive assessment steps: (A) maximum intensity projections (MIPs) of DWI, (B) DWI and apparent diffusion coefficient maps, (C) as (B) but with additional native T1- and T2-weighted images, and (D) as (C) but with additional CE images (full-length protocol). Two readers independently determined the presence of a suspicious lesion. Histological confirmation was obtained for conspicuous lesions, whereas the full MRI data set was obtained for inconspicuous and clearly benign lesions. Statistical analysis included calculation of diagnostic accuracy and interrater agreement via the intraclass correlation coefficient. Results The cohort comprised 116 cases with BI-RADS 1 findings and 138 cases with BI-RADS >= 2 findings, including 38 histologically confirmed malignancies. For (A), breasts without pathological findings could be recognized with high diagnostic accuracy (negative predictive value, >= 97.0%; sensitivity, >= 92.1% for both readers), but with a limited specificity (>= 58.3%; positive predictive value, >= 28.6%). Within the native readings, approach (C) with b2500 performed best (negative predictive value, 99.5%; sensitivity, 97.4%; specificity, 88.4%). The intraclass correlation coefficient was between 0.683 (MIP b1500) and 0.996 (full protocol). Conclusions A native abbreviated breast MRI protocol with advanced high b-value DWI might allow nearly equivalent diagnostic accuracy as CE breast MRI and seems to be well suited for lesion detection purposes.
CRIS-Team WoS Importer:2021-10-01